MOTIVASI TOKOH MASYARAKAT MENGIKUTI OLAHRAGA PENCAK SILAT PERSAUDARAAN SETIA HATI TERATE DI DESA BANGUNREJO KIDUL - Yoyok Davit Rahadika; Kuncoro Darumoyo; Kartika Septianingrum (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
“This study explores the motivation of community leaders in Bangunrejo Kidul Village in participating in the Persaudaraan Setia Hati Terate (PSHT) pencak silat training. Pencak silat is a traditional Indonesian martial art that is popular at the national and international levels. PSHT, which was founded in 1922, teaches the values ​​of noble character and family. This study uses a descriptive qualitative approach with a case study, involving interviews, observations, and documentation. The main focus of the study includes the motivation of community leaders, as well as supporting and inhibiting factors in their participation. The results showed that the main motivations of community leaders were cultural preservation, health, and brotherhood. Supporting factors included the training model for the elderly and the strength of family ties in PSHT. In contrast, the main inhibitors were declining physical condition and time constraints due to family and work responsibilities. These findings provide insight into the challenges and motivations in pencak silat participation, as well as recommendations for the future development of this sport.”